2022
DOI: 10.1111/1752-1688.12996
|View full text |Cite
|
Sign up to set email alerts
|

DSWEmod — The Production of High‐Frequency Surface Water Map Composites from Daily MODIS Images

Abstract: Optical satellite imagery is commonly used for monitoring surface water dynamics, but clouds and cloud shadows present challenges in assembling complete water time series. To test whether the daily revisit rate of Moderate Resolution Imaging Spectroradiometer (MODIS) satellite imagery can reduce cloud obstruction and improve high‐frequency surface water mapping, we compared map results derived from Landsat (30‐m) and MODIS (250‐m) data across the state of California for 2003–2019. We adapted the Dynamic Surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…To test the accuracy of DSWEmod at a national scale, we implemented a stratified random sampling approach (Stehman & Foody, 2019) based on Level I Ecoregions; this approach is modeled after Soulard et al. (2022). We selected random samples for each ecoregion within maximum water footprints (1985‐2019) determined by an independent water product, JRC (Pekel et al., 2016), hereafter referred to as the JRC maximum water stratum.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To test the accuracy of DSWEmod at a national scale, we implemented a stratified random sampling approach (Stehman & Foody, 2019) based on Level I Ecoregions; this approach is modeled after Soulard et al. (2022). We selected random samples for each ecoregion within maximum water footprints (1985‐2019) determined by an independent water product, JRC (Pekel et al., 2016), hereafter referred to as the JRC maximum water stratum.…”
Section: Methodsmentioning
confidence: 99%
“…However, data continuity is paramount in trend analysis, and techniques aiming to test the temporal limits of trend analysis using optical imagery data must measure the influence of cloud obstruction in creating data gaps. Soulard et al (2022) concluded that complete, cloud-free monthly records spanning multiple decades represent a reasonable temporal resolution for applications focused on intra-and inter-annual surface water dynamics. Recent literature suggests that dense time series are well-suited to capture processes of land surface change at monthly scales (Senay et al, 2017;Tulbure & Broich, 2013;Waylen et al, 2014).…”
Section: Trends In Surface Water Extentmentioning
confidence: 99%
See 3 more Smart Citations